The Influence of Some Axial Ligands on Ruthenium–Phthalocyanine Complexes: Chemical, Photochemical, and Photobiological Properties - Martins, Tássia Joi; Negri, Laisa Bonafim; Pernomian, Laena; Faial, Kelson do Carmo Freitas; Xue, Congcong; Akhimie, Regina N.; Hamblin, Michael R.; Turro, Claudia; da Silva, Roberto S. (Frontiers in Molecular Biosciences, 2021)
This work presents a new procedure to synthesize ruthenium-phthalocyanine complexes and uses diverse spectroscopic techniques to characterize trans-[RuCl(Pc)DMSO] (I) (Pc = phthalocyanine) and trans-[Ru(Pc)(4-ampy)2] (II) (4-ampy = 4-aminopyridine). The triplet excited-state lifetimes of (I) measured by nanosecond transient absorption showed that two processes occurred, one around 15 ns and the other around 3.8 µs. Axial ligands seemed to affect the singlet oxygen quantum yield. Yields of 0.62 and 0.14 were achieved for (I) and (II), respectively. The lower value obtained for (II) probably resulted from secondary reactions of singlet oxygen in the presence of the ruthenium complex. This work also investigates how axial ligands in the ruthenium-phthalocyanine complexes affect their photo-bioactivity in B16F10 murine melanoma cells. In the case of (I) at 1 µmol/L, photosensitization with 5.95 J/cm2 provided B16F10 cell viability of 6%, showing that (I) was more active than (II) at the same concentration. Furthermore, (II) was detected intracellularly in B16F10 cell extracts. The behavior of the evaluated ruthenium-phthalocyanine complexes point to the potential use of (I) as metal-based drug in clinical therapy. Changes in axial ligands can modulate the photosensitizer activity of the ruthenium phthalocyanine complexes.